2009
DOI: 10.1071/fp08269
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 accelerates flag leaf senescence in wheat due to ear photosynthesis which causes greater ear nitrogen sink capacity and ear carbon sink limitation

Abstract: It was anticipated that wheat net photosynthesis would rise under elevated CO 2 , and that this would alter the progress of senescence due to the unbalance of carbohydrates and nitrogen. Our study showed that ear carbon sink was limited, and sugar was accumulated, hexokinase activities and levels of phosphorylated sugar were increased within the flag leaves, grain nitrogen sink capacity was enhanced, and flag leaf senescence was accelerated under elevated CO 2 . However, if the ear of the main stem was covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 42 publications
(61 reference statements)
1
35
0
1
Order By: Relevance
“…Amino acid concentration in the leaf was determined by the Ninhydrin method [33] using L-leucine as the standard. Soluble carbohydrates and starch were determined following the method of Zhu et al [34] using sucrose as the standard. …”
Section: Methodsmentioning
confidence: 99%
“…Amino acid concentration in the leaf was determined by the Ninhydrin method [33] using L-leucine as the standard. Soluble carbohydrates and starch were determined following the method of Zhu et al [34] using sucrose as the standard. …”
Section: Methodsmentioning
confidence: 99%
“…For example, Ommen et al [25] used chlorophyll as a marker to conclude accelerated senescence in wheat, and García et al [66] interpreted a lower than expected CO 2 -stimulation of carbon assimilation during later developmental stages as accelerated senescence. Zhu et al [23] and Fangmeier et al [26] suggested that leaf senescence was accelerated as a result of changes in the relative demand of the developing spikes for N and C (relatively greater N sink strength of the spike). In contrast to some of these suggestions, our chlorophyll measurements (using SPAD values as a proxy) give no evidence that elevated [CO 2 ] accelerated leaf senescence ( Fig.…”
Section: Expression Patterns During Senescencementioning
confidence: 98%
“…As carbon assimilation increases and N concentration decreases under elevated [CO 2 ], tissues can have greater C/N ratios, and altered metabolite concentrations [22][23][24]. Elevated [CO 2 ] may also change leaf senescence: In cereals such as wheat and barley, changes in leaf functioning under elevated [CO 2 ] were ascribed to accelerated senescence processes, marked as faster chlorophyll decline [25].…”
Section: Introductionmentioning
confidence: 98%
“…For example, plants photosynthetically acclimate (i.e., downregulate) to growth in elevated [CO 2 ] through changes in the photosynthetic apparatus, including lower light-and CO 2 -saturated photosynthesis (A max ) as well as lower V cmax (maximum Rubisco carboxylation) and J max (maximum electron transport) (Tissue et al 1993(Tissue et al , 2001. A second process that may impact the long-term enhancement of photosynthesis under elevated [CO 2 ] is reduced N availability, such as through re-allocation of N within the plant to meet other growth needs (Theobald et al 1998;Zhu et al 2009) or reduced N cycling in the ecosystem (Zak et al 2000). Support for this process comes from meta-analyses of both FACE (free-air carbon dioxide enrichment) and OTC (open-top chamber) studies: some plants, but particularly woody species, that exhibit photosynthetic acclimation also exhibit declines in leaf N and Rubisco content Ainsworth and Long 2005).…”
Section: Introductionmentioning
confidence: 99%